2020
DOI: 10.1186/s40168-020-00845-6
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota-derived indole 3-propionic acid protects against radiation toxicity via retaining acyl-CoA-binding protein

Abstract: Background: We have proved fecal microbiota transplantation (FMT) is an efficacious remedy to mitigate acute radiation syndrome (ARS); however, the mechanisms remain incompletely characterized. Here, we aimed to tease apart the gut microbiota-produced metabolites, underpin the therapeutic effects of FMT to radiation injuries, and elucidate the underlying molecular mechanisms. Results: FMT elevated the level of microbial-derived indole 3-propionic acid (IPA) in fecal pellets from irradiated mice. IPA replenishm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
107
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(112 citation statements)
references
References 59 publications
5
107
0
Order By: Relevance
“…The major function of the gut microbiota is to help in the harvesting of nutrients and energy from our diet. Moreover, it participates in the development of a host’s immune system, brain, and behavior; protects against pathogens; and is a factory of bioactive compounds [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The major function of the gut microbiota is to help in the harvesting of nutrients and energy from our diet. Moreover, it participates in the development of a host’s immune system, brain, and behavior; protects against pathogens; and is a factory of bioactive compounds [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, FMT is also shown to be an efficacious remedy to mitigate acute radiation syndrome. Recent study [ 100 ] confirmed that indole 3-propionic acid is a key intestinal microbiota metabolite corroborating the therapeutic effects of FMT to radiation toxicity.…”
Section: Interplay Between the Gut Microbiome And Radiotherapy Toxicimentioning
confidence: 81%
“…To exploit the many microbiota and functional changes observed with animal models in response to radiation, studies have been done to evaluate the usefulness of microbiota-derived short-chain fatty acids and other metabolic products as potential MCMs, to either prevent or mitigate radiation-induced GI injury. In a study in which FMT was given to irradiated mice, analysis of fecal pellets showed that a microbial molecule-indole 3-propionic acid (IPA)-was present at high levels (Xiao et al, 2020). Believing that this molecule could be responsible for the observed radiation protection obtained with FMT, oral IPA alone was provided to another group of irradiated animals.…”
Section: Preclinical Fmt Studiesmentioning
confidence: 99%
“…Other studies found oral gavage of IPA and microbiota-derived valeric acid (VA) provided protection against up to 7 Gy, and, in the case of VA, mitigated GI radiation injury when given post-TAI (12 Gy). VA was found to prevent intestinal inflammation and dysfunction, and maintain microbiota compositional patterns Xiao et al, 2020).…”
Section: Preclinical Fmt Studiesmentioning
confidence: 99%